Avaliação do perfil de biomarcadores imunológicos no perfil clínico de pacientes com anemia falciforme - Silva Junior, Alexander Leonardo (2020)
Introduction: Sickle cell disease is the most common monogenic disorder around the world. The mutation leads to a shift on hemoglobin molecule, which takes to hemolysis condition, marked mainly during acute inflammatory crisis and characterized by immune system activation. The molecule participation as chemokines, anaphylatoxins, cytokines and growth factors released specially by leukocytes and endothelial cells increase the risk to develop vaso-occlusive crisis and so, the clinical complications observed in these patients. Due to immune molecule influence on sickle cell physiopathology, under different clinical status, related to scarcity of biomarkers studies, we highlight the need to characterize the concentration of these proteins on inflammatory state of sickle cell. Objective: Evaluate the immunological profile of patients with sickle cell anemia under different clinical status accompanied at Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas (HEMOAM). Materials and methods: This is a longitudinal study which used biological samples of 53 healthy blood donors, 27 patients with sickle cell anemia in steady-state condition, 22 patients in acute vaso-occlusive crisis, in which were accompanied with one more sample collection, at convalescence. The samples were from previous projects approved by CEP-HEMOAM. The blood count was performed with whole blood, while serum was used to quantification of cytokines, chemokines and growth factors by Luminex technic, with the kit BioPlex Pro-Human Cytokine 27-Plex from BioRad at FIOCRUZ-MG and analyzed by BioPlex Manager software. Anaphylatoxins were measured at Fundação HEMOAM by Cytometric Bead Array technic, with kit The BD CBA Human Anaphylatoxin, and FCAP Array software was used for acquisition. Statistical analysis was performed on GraphPad Prism v. 5.0 software, with confidence interval of 95% and p < 0.05 as statistically significant. Correlation network was performed on software Cytoscape v. 3.1. and heatmaps on software R 3.0.1. Results: We identified higher concentration of IL-2, IL-4, IL-5, IL-7, PDGF-BB and G-CSF on vaso-occlusive patients, which further demonstrates a biomarker signature to this clinical condition. Other molecules showed different concentration under clinical profile, but were not exclusive only to crisis status. IL-10, IL-1ra and IL-1β concentration were identified by bioinformatics technics as potential markers to cluster patients under clinical condition. In convalescence condition, CXCL8, CCL4, IL-1ra and PDGF-BB showed potentiality as laboratorial markers of follow-up after crisis. Correlation analysis showed higher relation of molecules in crisis condition, which reduced through convalescence until steady-state. Conclusion: Vaso-occlusive crisis profile is marked by anti-inflammatory and cell proliferation cytokines. IL-1ra and PDGF-BB are potential candidates as laboratorial markers to laboratorial recovery, and serum concentration of IL-10, IL-1ra and IL-1β might be used to characterize the clinical status of sickle cell patient. More studies must be conducted to evaluate the potentiality of these molecules on clinical progression, on prognosis and follow- up of these patients after crisis.